(untitled) (Al-Academy, 2015)
The present research deals with studying the formal variations for the Quranic calligraphy at the beginning of Islam , as being regarded from the original Arabic calligraphies which were developed later till they became as they are now, where the calligraphers in pushing for simulating these original calligraphies and knowing the methods of their writing by the calligraphers at that time.That helped in enriching and developing the aesthetic and designing valuesFor these calligraphies, as being calligraphic achievements represent transmission resulted from the objective, aesthetic and indicative vision in producing the verses according to a certain form. This has a clear impact in tendency to the technical, aesthetic and expressing development in producing designing structures unlimited with certain letters or a general building for the page.Through the surveying study, research and models which where obtained , the researcher was able to give the problems of his research the following question :What are the formal variations for the quranis calligraphy at the beginning of Islam?The importance of the research embodied through the interest with the calligraphies which were about to vanish because of the rarity of using them. The formal variations are being clarified by showing the forms of the letters of these calligraphies and the advantage which is being presented by the study for the researchers and scholars in the domain of knowing these calligraphies. This study aimed at discovering the formal variations for the quranic calligraphy at the beginning of Islam through determining the formal variations for the letters, the general building of the page and the method in which they have been written in limits of calligraphic models which arrived to us, in the calligraphy which is called madani and makain during the first hundreds years from the beginning of Islam. The second chapter deals with the theoretical frame which contained the writing of Quran in the era of messenger (peace to upon him) , and the materials which the Qurans were written on at the beginning of Islam . The third chapter contained the procedure of the research. The fourth chapter deals with analyzing the samples and showing the results, conclusions recommendations and proposals.